Molecular mass ranges of coal tar pitch fractions by mass spectrometry and size-exclusion chromatography - KARACA ALBAYRAK, FATMA (WILEY, 2009)
A coal tar pitch was fractionated by solvent solubility into heptane-solubles, heptane-insoluble/toluene-solubles (asphaltenes), and toluene-insolubles (preasphaltenes). The aim of the work was to compare the mass ranges of the different fractions by several different techniques. Thermogravimetric analysis, size-exclusion chromatography (SEC) and UV-fluorescence spectroscopy showed distinct differences between the three fractions in terms of volatility, molecular size ranges and the aromatic chromophore sizes present. The mass spectrometric methods used were gas chromatography/mass spectrometry (GC/MS), pyrolysis/GC/MS, electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICRMS) and laser desorption time-of-flight mass spectrometry (LD-TOFMS). The first three techniques gave good mass spectra only for the heptane-soluble fraction. Only LDMS gave signals from the toluene-insolubles, indicating that the molecules were too involatile for GC and too complex to pyrolyze into small molecules during pyrolysis/GC/MS. ESI-FTICRMS gave no signal for toluene-insolubles probably because the fraction was insoluble in the methanol or acetonitrile, water and formic acid mixture used as solvent to the ESI source. LDMS was able to generate ions from each of the fractions. Fractionation of complex samples is necessary to separate smaller molecules to allow the use of higher laser fluences for the larger molecules and suppress the formation of ionized molecular clusters. The upper mass limit of the pitch was determined as between 5000 and 10000 u. The pitch asphaltenes showed a peak of maximum intensity in the LDMS spectra at around m/z 400, in broad agreement with the estimate from SEC. The mass ranges of the toluene-insoluble fraction found by LDMS and SEC (400-10 000 u with maximum intensity around 2000 u by LDMS and 100-9320 u with maximum intensity around 740 u by SEC) are higher than those for the asphaltene fraction (200-4000 u with maximum intensity around 400 u by LDMS and 100-2680 u with maximum intensity around 286 u by SEC) and greater than values considered appropriate for petroleum asphaltenes (300-1200 u with maximum intensity near 700 u). Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: UV-FLUORESCENCE SPECTROSCOPY; COMPOSITIONALLY DISTINCT COMPONENTS; ANALYZING PETROLEUM ASPHALTENES; ATOMIC-FORCE MICROSCOPY; CONTRASTING PERSPECTIVE; SOLUBLE FRACTIONS; LIMITATIONS; RESOLUTION; MIXTURES; LIQUIDS